The procedures used by the translator in translating Cultural Terms in “To All the Boys I’ve Loved Before” novel by Jenny Han to its Indonesian translation - Cattleya Wahyu Pravitha (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2019)
This study aims at analyzing the translation procedures used by the translator in translating cultural terms in a novel entitled “To All the Boys I’ve Loved Before” by Jenny Han. The sources of the data are the English version of the novel and its Indonesian translation. The cultural terms are analyzed using the translation procedures of Newmark. The method used in this study is descriptive qualitative. The cultural terms are listed and categorized, thus are analyzed .This study found out that the procedures most used by the translator in translating the cultural terms are transference. DOI: 10.26905/enjourme.v4i2.3836